Potentially Inappropriate Prescribing (PIP) based on Beers Criteria in Geriatric Patients at the Inpatient Unit of a Hospital in Bandar Lampung - Citra Yuliyanda Pardilawati; Jessy Dewi Awali; Tri Umiana Soleha; Rasmi Zakiah Oktarlina; Yulianasari Pulungan (Jurusan Farmasi Fakultas Kedokteran Universitas Lampung, 2025)
Geriatric patients often experience polypharmacy due to multimorbidity. This is a factor that increase the risk of Potentially Inappropriate Prescribing (PIP), which can cause serious health problems. Beers Criteria are one of the guidelines used to identify PIP in geriatric patients. This study aims to evaluate PIP in geratric patients using Beers criteria. This study used a cross-sectional approach. The sampling technique was purposive sampling. The study subjects were the medical records of geriatric patients at the inpatient installation of one of the hospitals in Bandar Lampung, totaling 76 subjects. Geriatric patients at the inpatient unit of one of the hospitals in Bandar Lampung were predominantly male with 48 (63.2%) patients, aged group 60 – 69 years with 45 (59.2%) patients, and receiving ≥5 types of medications with 74 (97.4%) patients. The incidence of PIP was found in 26 (34.2%) patients with a total of 33 PIP events consisting of PIP category 1, 2 and 4, are 16 (48.48%), 9 (27.27%) and 8 (24.24%) events respectively.